The New Filipino cookbook : creative variations of traditional recipes - Subida, Rory, editor (Pasig City, 2005)
Presents a modern twist on classic Filipino dishes, showcasing innovative takes while preserving their cultural roots. The book features contributions from various chefs and home cooks, blending tradition with creativity to inspire a new generation of Filipino cuisine lovers.
Keywords: Cookery, Philippine